House cricket personality tests based on emergence behaviour in experimental trials - Low, Matthew (Swedish University of Agricultural Sciences, 2022)
Data Material: refer to 'Description of the dataset'
Purpose of the study: These data primarily relate to the scientific article "Viral infection changes the expression of personality traits in an insect species reared for consumption". This is summarised in the following abstract: Disease-induced personality change results from endogenous and adaptive host responses or parasitic manipulation. Within animal husbandry systems understanding the connection between behaviour and disease is important for health monitoring and for designing systems considerate to animal welfare. However, understanding these relationships within insect mass-rearing systems is still in its infancy. We used a simple repeated behavioural-emergence test to examine parasite-induced differences in group personality traits in the house cricket Acheta domesticus, by comparing the behaviours of 37 individuals infected with the Acheta domesticus densovirus (AdDV) and 50 virus-free individuals. AdDV-infected animals had a much lower emergence probability, longer times until emergence, and did not change their behaviour with experience compared to the virus-free animals. AdDV-infected animals also had lower variation in their probability of emergence within the population, most likely related to animals displaying a relatively uniform sickness response. These infected animals also had higher variation in their response to experimental trial experience; this greater variation resulted from a difference between males and females. Infected females responded to experience in a similar way as virus-free animals, while AdDV-infected males showed a response to experience in the opposite direction: i.e., while all other groups reduced emergence time with experience, infected males always increased their mean emergence time as trials progressed. Our results are important not only in the context of animal personality research, but also with regards to creating husbandry systems and disease monitoring within the insects-as-food industry that are considerate to both production traits and animal welfare.

The dataset file ‘Personality_data_virus_infection_SciRep_pub.csv’ is a simple csv datafile with 6 columns and 575 rows of data from 87 individual house crickets that were involved in repeated personality testing based on their emergence time from a tube in a novel environment (see the paper “Viral infection changes the expression
of personality traits in an insect species reared for consumption” by Low et al.)
During each experimental trial each cricket was individually placed into a tube and the time recorded to it to emerge, and based on multiple measurements this allowed measures of its ‘personality’. The study was concerned with differences in emergence behaviour for crickets that were infected with Acheta domesticus
densovirus (N=37) and individuals that were certified as virus free (N=50). Experimental trials were repeated for each animal every day or every second datyduring the data collection period.
See the documentation file 'data_description_SciRep.pdf' for information about each data column.

Dessa data avser främst den vetenskapliga artikeln "Viral infection changes the expression of personality traits in an insect species reared for consumption". Här undersöker vi beteendeegenskaperna hos både infekterade och friska syrsor och relaterar skillnader i dessa egenskaper till en förståelse av insektspersonligheter inom ett djurproduktionssystem. Se engelsk beskrivning för närmare information.

För en fullständig beskrivning av data, se den engelska versionen
Hussyrsors personlighetstest baserade på uppkomstbeteende i experimentella försök - Hussyrsor personlighetstest baserade på uppkomstbeteende i experimentella försök
Keywords: Densovirinae; Densovirinae; INSECTS; VIRUSES; behavioural science; beteendeforskning; insect; insekter; virus; virus; densovirus; densovirus; insect; insekt; house cricket; hussyrsor; Acheta domesticus; Acheta domesticus; virus; virus; personality research; personlighetsforskning; Zoology; Zoologi; Ecology; Ekologi; Behavioural Sciences Biology; Etologi; Evolutionary Biology; Evolutionsbiologi; Other Veterinary Science; Annan veterinärmedicin